Islamisasi di Pulau Jawa dalam Perspektif Asimilasi Budaya - Naja, Anang Darun (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2021)
Islamic religious education todays is faced with various situations, in fact, Nowdays, there are many faces of Islam; violenes, coercive, and unacceptable to differences, this is very contrary to the socio-culture and geographical area of ​​the very diverse Indonesian society. Therefore, today the face of education in accordance with what our predecessors have taught us in the form of spreading Islam with cultural assimilation in the archipelago needs to be applied in the world of education. This article is a literary research on the process of Islamization on the island of Java. The author finds that a peaceful education teaching pattern that respects the diversity of Indonesian society needs to be applied to students to create a moderate Islamic character.